Deficit Financing: Implications and Management - Thapa, Govinda Bahadur (NRB Economic Review, 2005)
Developing countries usually mobilize part of their resources by borrowing from internal as well as external sources to finance their development activities. These sources gradually build up the debt stock of the country. Such debt stock demands regular debt servicing, that is, principal and interest payment, which consumes scarce resources that can be used for financing development. Therefore, excessive deficits and heavy borrowing to finance that deficit drain out the resources of the developing countries. Liquidity is also involved while borrowing and servicing. Thus, both of these transactions are conducted in such a way that the country concerned always finds itself in a comfortable position with regard to the liquidity, which is known as the debt management.